Pharmacotherapy for post-traumatic stress disorder: Systematic review and meta-analysis. (February 2015) - Hoskins, Mathew; Pearce, Jennifer; Bethell, Andrew; Dankova, Liliya; Barbui, Corrado; Tol, Wietse A.; van Ommeren, Mark; de Jong, Joop; Seedat, Soraya; Chen, Hanhui; Bisson, Jonathan I.
Abstract : Background: Pharmacological treatment is widely used for post-traumatic stress disorder (PTSD) despite questions over its efficacy. Aims: To determine the efficacy of all types of pharmacotherapy, as monotherapy, in reducing symptoms of PTSD, and to assess acceptability. Method: A systematic review and meta-analysis of randomised controlled trials was undertaken; 51 studies were included. Results: Selective serotonin reuptake inhibitors were found to be statistically superior to placebo in reduction of PTSD symptoms but the effect size was small (standardised mean difference −0.23, 95% CI −0.33 to −0.12). For individual pharmacological agents compared with placebo in two or more trials, we found small statistically significant evidence of efficacy for fluoxetine, paroxetine and venlafaxine. Conclusions: Some drugs have a small positive impact on PTSD symptoms and are acceptable. Fluoxetine, paroxetine and venlafaxine may be considered as potential treatments for the disorder. For most drugs there is inadequate evidence regarding efficacy for PTSD, pointing to the need for more research in this area.